2016
DOI: 10.1016/j.ijppaw.2016.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Reduced helminth parasitism in the introduced bank vole ( Myodes glareolus ): More parasites lost than gained

Abstract: Introduced species are often less parasitised compared to their native counterparts and to ecologically similar hosts in the new environment. Reduced parasitism may come about due to both the loss of original parasites and low acquisition of novel parasites. In this study we investigated the intestinal helminth parasites of the introduced bank vole (Myodes glareolus) in Ireland. Results were compared to data from other European studies and to the intestinal helminth fauna of an ecologically similar native rode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 59 publications
(80 reference statements)
2
22
0
Order By: Relevance
“…Mitochondrial DNA analysis has indicated that the bank voles present in Ireland are most closely related to those in continental Europe, in particular native bank voles within Germany ( Stuart et al., 2007 ), for which one study found ten ecto- and endoparasite species ( Klimpel et al., 2007 ), although only a small number of voles (n = 29) were sampled. There is no doubt that the bank voles in Ireland have lost parasite diversity, and although we used broad taxa level identification, previous species-level identification has found that bank voles in Ireland are infected with only three helminth species ( Loxton et al., 2016 ), corroborating the parasite community observed in the present study. Consistent with the ‘lag effect’ we observed decreased parasite abundance with increasing distance from focal point or introduction to the invasion front, and stochastic loss of parasite taxa across the invasion gradient ( Fig.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Mitochondrial DNA analysis has indicated that the bank voles present in Ireland are most closely related to those in continental Europe, in particular native bank voles within Germany ( Stuart et al., 2007 ), for which one study found ten ecto- and endoparasite species ( Klimpel et al., 2007 ), although only a small number of voles (n = 29) were sampled. There is no doubt that the bank voles in Ireland have lost parasite diversity, and although we used broad taxa level identification, previous species-level identification has found that bank voles in Ireland are infected with only three helminth species ( Loxton et al., 2016 ), corroborating the parasite community observed in the present study. Consistent with the ‘lag effect’ we observed decreased parasite abundance with increasing distance from focal point or introduction to the invasion front, and stochastic loss of parasite taxa across the invasion gradient ( Fig.…”
Section: Discussionsupporting
confidence: 89%
“…One parasite genus that has almost certainly been lost in the Rep. of Ireland population is Heligmosomoides spp. ( Loxton et al., 2016 ). This genus is known to manipulate the immune system in order to avoid being expelled by the host ( Maizels et al., 2004 ) and the loss of it may have had knock-on effects for the remaining parasite community.…”
Section: Discussionmentioning
confidence: 99%
“…Where available, these were analysed using worm burden data ( Aelurostrongylus falciformis , Crenosoma spp., Uncinaria criniformis ) or faecal egg/larval counts ( Eucoleus aerophilus , Strongyloides spp., Species A, Unknown 1, 2). The mean species richness was calculated as a measure of the infracommunity (Loxton et al , 2016). Abundance and intensity were modelled using a modified negative binominal GLM (Loxton et al , 2016) from the MASS package in R (Venables and Ripley, 2002).…”
Section: Methodsmentioning
confidence: 99%
“…The mean species richness was calculated as a measure of the infracommunity (Loxton et al , 2016). Abundance and intensity were modelled using a modified negative binominal GLM (Loxton et al , 2016) from the MASS package in R (Venables and Ripley, 2002). Full factorial models incorporated measures of season (four levels: spring, summer, autumn, winter); region (two levels: east, west) and sex (two levels: female, male).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation